Subjugated and Disqualified Knowledge in Marketing Theory: Historical Struggles and the Conditions of Repudiation (Revista Interdisciplinar de Marketing, 2023)
When worldviews or claims to knowledge become widely accepted and increasingly ossified, this demands the mobilization of critical reflection. It is to be expected that such claims have achieved the status of received wisdom because they serve the interests of some groups, skew power relations, and assist in reaffirming the geopolitical status quo. Attention must thus be devoted to the “geopolitics of marketing theory” and its ramifications. In making this case, we engage with the writings proffered by thinkers from the Global South, whose critique is interlaced with hope, and promises to help make the marketing discipline relevant to most people on this planet, that is, those whose voices have been trammelled and denied in the march of Euro- and Americanocentric modernity.